(3MGTjI Ydi TQM GdQSGdI GdYVOjIs - (3eLghds
(3ChdgG (B:s
(3hHYO agPg aGFOI YLGH Hd RGFOI dG JONd ai GdMSGH Ydi GdTQM GdeTghQ s
(3BNQgG (B:s
(3hgh HjGf Cf GdeYGQVI dG jSJdRe GdJUOjb HGdfbjVjf s
(3GdQSGdI GdYVOjI GfXQ cTa GdXfhf L(B1 (3U` (B877s
(3GdfSNI HgG MhGTs
(3dg fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs